The Effect Of Human Resources Development On Employee Performance At Government Office In South Sumatra - Ferdy Leuhery; Ratnawita Ratnawita; Kunto Atmojo; Hermiyetti Hermiyetti; Halim Dwi Putra (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The purpose of this research is to analyze and test the effect of human resource development as a proxy for education & job training and promotion on employee performance in the South Sumatra Provincial Government Office. The population in this study were all employees in the South Sumatra Provincial Government Office. Samples were taken by accidental sampling so that a total of 100 people were obtained based on the Slovin method. Data were analyzed using IBM SPSS version 26 and data analysis through several tests, namely: validity test, reliability test, classical assumption test, multiple linear regression analysis and coefficient of determination test. The results showed that the development of human resources proxied by education & job training and promotions either partially or simultaneously had an influence on employee performance in the South Sumatra Provincial Government Office.